Four unusual mortality events of seabirds in the Patagonian Sea, 2000–2006: Species affected and possible causes - Uhart, Marcela María (2025)
The Patagonian Sea is a highly productive marine ecosystem and a hotspot for seabird diversity and density in the Southwest Atlantic Ocean. Reports of unusual mortality events are relatively scarce in this region, likely due to under detection and investigation. In this study, we report on four unusual mortality events affecting seabirds in the Patagonian Sea from 2000 to 2006. Events 1 and 2 occurred at Golfo Nuevo and Chubut coast, Argentina in September–December 2000, affecting at least 4550 seabirds, mainly Magellanic penguins (Spheniscus magellanicus). Event 3 occurred at the Falkland/Malvinas Islands during December 2002–January 2003, affecting at least 3500 seabirds, mainly gentoo penguins (Pygoscelis papua). Event 4 occurred at Punta Loma and Punta León, Argentina, in November 2006, affecting at least 57 seabirds, mainly kelp gulls (Larus dominicanus). The aetiology of Events 1 and 2 could not be determined, but malnutrition/starvation and paralytic shellfish poisoning, respectively, were identified as potential causes. Pathological findings and toxicological testing supported paralytic shellfish poisoning as the cause of Events 3 and 4. Our results illustrate how identifying the occurrence, cause and extent of unusual mortality events affecting seabirds can present significant challenges. Moreover, our investigations of the events display variations in timeliness and completeness, and our lack of certainty on aetiology reflects the shortcomings often faced in remote locations and low resource settings. Technological advances, such as smartphones, increased public awareness and connectivity, coupled with more and better equipped protected areas and diagnostic laboratories will likely aid in overcoming difficulties from past decades.